Superlocalization of excitons in carbon nanotubes at cryogenic temperature - Raynaud, C.; Graf, Arko; Zaumseil, Jana (Nano letters, 2019)
At cryogenic temperature and at the single emitter level, the optical properties of single-wall carbon nanotubes depart drastically from that of a one-dimensional (1D) object. In fact, the (usually unintentional) localization of excitons in local potential wells leads to nearly 0D behaviors such as photon antibunching, spectral diffusion, inhomogeneous broadening, etc. Here, we present a hyperspectral imaging of this spontaneous exciton localization effect at the single nanotube level using a super-resolved optical microscopy approach. We report on the statistical distribution of the trap localization, depth, and width. We use a quasi-resonant photoluminescence excitation approach to probe the confined quantum states. Numerical simulations of the quantum states and exciton diffusion show that the excitonic states are deeply modified by the interface disorder inducing a remarkable discretization of the excitonic absorption spectrum and a quenching of the free 1D exciton absorption.